Access to public information. A constitutional analysis of the spanish law - Moreno González, Gabriel (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
This paper analyzes the constitutional dimension of the right to access public information and especially, how it has been regulated in de recent Spanish Ley de Transparencia. Furthermore, it also answers the following questions regarding the right to access public information: a) who can invoke it?; b) what is its content?; c) does the law respect constitutional limits.